Numerical Approximations of Log Gaussian Cox Process (Student Abstract) - Buet-Golfouse, Francois; Roggeman, Hans (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
This paper considers a multi-state Log Gaussian Cox Process (`"LGCP'') on a graph, where transmissions amongst states are calibrated using a non-parametric approach. We thus consider multi-output LGCPs and introduce numerical approximations to compute posterior distributions extremely quickly and in a completely transparent and reproducible fashion. The model is tested on historical data and shows very good performance.